Development of Poultry Production Clusters in China: A Policy Review - Wang , Libin; Liu, Qiming; Zheng, Hong E.; Wu, Jin; Li, Xiaoyun (International Journal of Poultry Science, 2014)
The poultry sector is important for the livelihoods of rural people in China. Under increased public concerns on bio-security, how to integrate the small scale poultry producers into safe and high value production chains is a key political issue in many developing countries. In this context, China initiated a model of building poultry production clusters (PPCs) and moving small producers into the clusters so as to increase the scale of production as well as bio-security. It was considered an innovative model in China and the government issued various policies to promote this model since 2003. However, the model failed after a couple of years of practice. This paper reviews the social, economic and political elements of this endeavor and the impacts of PPCs in China. The main reason for the failure is that, without external authority, the small producers were fated into the dilemma of collection actions, which means that each individual will maximize individual interest with the expense of the public interest. The failure of PPCs supports the previous research results in that as income growth and urbanization increases consumer demand for food safety, the small producers could not meet those high food safety standards and the government has limited capacities to work with millions of small producers to encourage them to follow the same production standards. The political commitment to control transmissible disease outbreaks was given higher priority than the commitment to small producer development since it was difficult for the government to balance the two.